The role of non-governmental kindergartens in the social education of children with disabilities from the perspective of parents - جافر, د. مروان مظهر; علی, له‌نیا هاشم; حارس, رۆزی علی; مصطفى, بريسكه مه‌ریوان; احمد, ڕێژوان عوسمان (Sulaimani Journal for Humanities, 2025)
One of the most prominent features of the new era is the proliferation of children's social education institutions, which help families to educate and change behavior and even solve children's psychological and social problems, kindergartens They are one of the most important tools, they can play a role in the social development of children, since the stage coincides with the first five years of a child's life, which in the opinion of many psychologists and education experts, a sensitive and important stage He is a child and determines the direction of his life. What the researchers noticed is the increase in the number of children with disabilities in the kindergarten, so that parents feel this undesirable situation and sometimes resort to treatment They take kindergartens, as many of them will need assistance, even to the extent of providing classrooms and private teachers for them. The most important types of children's disabilities in kindergartens are (learning difficulties, hyperactivity, language delay, physical and intellectual disabilities). The research is a quantitative research and the type of method used is social survey method, in which survey forms were distributed to parents who have children with special needs, then analyzed according to the procedures The study population was all non-governmental kindergartens in Sulaimani, which number (34) kindergartens. The sample of the study were several specific units of these kindergartens, after the completion of all Field Procedures Finally, the results are presented and then the study concludes with suggestions and recommendations.